Dark chocolate exacerbates acne. (29th December 2015) - Vongraviopap, Saivaree; Asawanonda, Pravit
Abstract: The effects of chocolate on acne exacerbations have recently been reevaluated. For so many years, it was thought that it had no role in worsening acne. To investigate whether 99% dark chocolate, when consumed in regular daily amounts, would cause acne to worsen in acne‐prone male subjects, twenty‐five acne prone male subjects were asked to consume 25 g of 99% dark chocolate daily for 4 weeks. Assessments which included Leeds revised acne scores as well as lesion counts took place weekly. Food frequency questionnaire was used, and daily activities were recorded. Statistically significant changes of acne scores and numbers of comedones and inflammatory papules were detected as early as 2 weeks into the study. At 4 weeks, the changes remained statistically significant compared to baseline. Dark chocolate when consumed in normal amounts for 4 weeks can exacerbate acne in male subjects with acne‐prone skin.